Review of The First American Music Conference at the University of Keele, The Literature of American Music, Ed. David Horn, Charles Ives and the American Band Tradition: A Centennial Tribute by Jonathon Elkus, The American Music Handbook by Christopher Pa - Potter, Keith (Contact: A Journal for Contemporary Music (1971-1990), 1975)